2023
DOI: 10.3390/cells13010015
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Effects of Autoantibodies in Autoimmune Encephalitides

Matias Ryding,
Anne With Mikkelsen,
Mette Scheller Nissen
et al.

Abstract: The heterogeneity of autoantibody targets in autoimmune encephalitides presents a challenge for understanding cellular and humoral pathophysiology, and the development of new treatment strategies. Thus, current treatment aims at autoantibody removal and immunosuppression, and is primarily based on data generated from other autoimmune neurological diseases and expert consensus. There are many subtypes of autoimmune encephalitides, which now entails both diseases with autoantibodies targeting extracellular antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 236 publications
0
6
0
Order By: Relevance
“…Gong et al reported a 56-year-old man with seizures and cognitive impairment diagnosed with PLE associated with SOX1 and GABAB antibodies and a poor outcome following SCLC detection [12] . Lastly, anti-GAD65 antibodies are reported to have questionable pathogenic significance and patients with autoimmune encephalitis should be evaluated for other antibodies against cell-surface antigens [21] , [22] , [23] . Nonetheless, overlapping encephalitis is rare, and its pathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al reported a 56-year-old man with seizures and cognitive impairment diagnosed with PLE associated with SOX1 and GABAB antibodies and a poor outcome following SCLC detection [12] . Lastly, anti-GAD65 antibodies are reported to have questionable pathogenic significance and patients with autoimmune encephalitis should be evaluated for other antibodies against cell-surface antigens [21] , [22] , [23] . Nonetheless, overlapping encephalitis is rare, and its pathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is not complement-mediated and is generally reversible. Activation of the ephrin type B2 can prevent this process (12,14). Lynch et al proposed that the antibody effect is dependent on NMDAR subtypes, where antibodies cause hyperfunction or hypofunction at extrasynaptic or synaptic NMDARs, respectively (14).…”
Section: Discussionmentioning
confidence: 99%
“…While infection may not directly induce antibody production, it likely plays a significant auxiliary role in facilitating antibody penetration across the blood–brain barrier (BBB) by increasing its permeability. Recently, studies on genetic predisposition in AE have yielded promising findings, with certain human leukocyte antigen (HLA) genes strongly associated with other forms of AE ( 12 ). Although no established HLAs have been linked to anti-NMDAR encephalitis, associations with HLA-A and HLA-DRB1 have been reported ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-mediated encephalitis is a heterogeneous group of disorders caused by more than 21 different antibodies ( 164 ). Among these, anti-LGI1 and anti-CASPR2 encephalitis are related to IgG4 as the dominant immunoglobulin subtype ( 165 ).…”
Section: Features Of Autoantibodies In Igg4-mediated Diseasesmentioning
confidence: 99%
“…CASPR2 serves as a transmembrane cell adhesion protein that interacts with Kv1.1 and Kv1.2 VGKCs in the juxtaparanodal region of myelinated peripheral nerves. In addition to its distribution in the nodes of Ranvier across the central and peripheral nervous systems, CASPR2 is also found in the synapses of the limbic system and basal ganglia ( 164 ). In mice, intrathecal infusion of anti-CNTN2 IgG, comprising a mixture of IgG1 and IgG4, purified from individuals with anti-CASPR2 encephalitis, were observed to induce memory deficits.…”
Section: Features Of Autoantibodies In Igg4-mediated Diseasesmentioning
confidence: 99%